1994
DOI: 10.1172/jci117497
|View full text |Cite
|
Sign up to set email alerts
|

Induction of beta-platelet-derived growth factor receptor in rat hepatic lipocytes during cellular activation in vivo and in culture.

Abstract: Invest. 1994Invest. . 94:1563Invest. -1569

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
199
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(208 citation statements)
references
References 40 publications
9
199
0
Order By: Relevance
“…These changes include the expression of new receptors, such as platelet-derived growth factor  receptors 1 and 2. Other receptors, such as the receptor for insulin-like growth factor 1 and endothelin are present on both quiescent and activated HSCs [4,5]. Several soluble factors, including growth factors, cytokines, chemokines and oxidative stress products, play a role in the activation of HSCs.…”
Section: Introductionmentioning
confidence: 99%
“…These changes include the expression of new receptors, such as platelet-derived growth factor  receptors 1 and 2. Other receptors, such as the receptor for insulin-like growth factor 1 and endothelin are present on both quiescent and activated HSCs [4,5]. Several soluble factors, including growth factors, cytokines, chemokines and oxidative stress products, play a role in the activation of HSCs.…”
Section: Introductionmentioning
confidence: 99%
“…PDGF is the most potent proliferating stimulus for HSCs (4,8). It has been reported that the PDGF receptor (PDGFR) is up-regulated along with HSC activation in carbon tetrachloride (CCl4)-and bile duct ligation-induced liver injuries (9)(10)(11). Dominant-negative soluble PDGFR or anti-sense PDGF gene transfer significantly attenuated experimental liver fibrosis development (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Induction of PDGF-B and PDGFRb in HSC is well documented in single-dose carbon tetrachloride (CCl 4 )-induced acute liver injury and during early stages of bile duct ligation (BDL). 4,5 Of the newly discovered isoforms, PDGF-C and -D, only PDGF-D showed significant upregulation in the BDL rat model. 3 Previous experiments using the CCl 4 model were confined to a period of 1-2 weeks and mainly represented single-dose CCl 4 applications.…”
mentioning
confidence: 99%